Penerapan Model Klasifikasi K-Nearest Neighbor Dalam Pencarian Kesesuaian Pekerjaan - Mutammimul Ula; Ria Zulhusna; Rizki Putra Fhonna; Angga Pratama (LPPM Universitas Mulia, 2022)
The application of job suitability is very important for companies/institutions in seeing the advantages of job applicants in accordance with their fields. then mobile-based information technology in finding job vacancies for applicants is very much needed for the required vacancies information and the suitability of the required formations. so that applicants can easily see the jobs that applicants need. The focus of this research problem is the existence of a mobile application in classifying job vacancies and the existence of a job information search menu according to the skills possessed and in accordance with the needs of mobile application-based jobs using the k-nearest neighbor (KNN) model. The purpose of this research is to apply a freelance application in aceh to help job search information according to the skills they have that match the needs of the job. The criteria available in the mobile application consist of a list of jobs, self-registration, a list of self-data weights, criteria and weights for recent education, work experience, marital status. The study was conducted with test data used 25 samples and applicants who registered consisted of 30 participants. the test results for the first registrant with the results of age 1, gender 0.5, GPA, 0.8, work experience 0.25, marital status 1 and passed with the value of the KNN calculation result is 0.406, the second applicant passed with a value of 0, 89 and the third did not pass with a value of 0.392. Job vacancies are obtained by taking 11 training data pieces that have the closest Euclidean distance to the questionnaire results. Furthermore, to test the accuracy using 30 samples with 24 accurate results and 6 inaccurate results.